2020
DOI: 10.1155/2020/8892349
|View full text |Cite
|
Sign up to set email alerts
|

Blind Photograph Watermarking with Robust Defocus-Based JND Model

Abstract: Just noticeable distortion (JND) is widely employed to describe the perception redundancy in the quantization-based watermarking framework. However, the existing JND models are generally constructed to treat every region of the photograph with an equal focus level, whereas the defocus effect has never been considered. In this paper, the defocus feature, which can portray the aesthetic emphasis in the photograph, is provided to improve the perceptual JND model. Firstly, two indicators which consider the block e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…e results show that the subjects' visual efficacy is the best under the illumination of more than 900 LX, and the illumination between 400 and 500 LX makes the subjects feel the most comfortable. It is suggested that the visual comfort factor should be properly considered in the lighting environment in pursuit of efficient work and mental stimulation [7]. Kumar et al studied the visual comfort of subjects in screen reading and paper reading under different combinations of illumination and color temperature in a small office space through a subjective evaluation experiment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e results show that the subjects' visual efficacy is the best under the illumination of more than 900 LX, and the illumination between 400 and 500 LX makes the subjects feel the most comfortable. It is suggested that the visual comfort factor should be properly considered in the lighting environment in pursuit of efficient work and mental stimulation [7]. Kumar et al studied the visual comfort of subjects in screen reading and paper reading under different combinations of illumination and color temperature in a small office space through a subjective evaluation experiment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From Table 3, it can be seen that the proposed method performs a better result. The BERs of the proposed method are about 5% lower than the method Wang et al 11 in JPEG60 + GN attacks, which is a valuable improvement. The BERs of the proposed method are about 1% lower than the method Wang et al 10 in JPEG60 + SPN and JPEG60 + Scaling attacks.…”
Section: Resultsmentioning
confidence: 77%
“…Then, the defocusing feature map is obtained by integrating the influence of surrounding blocks, and it is applied to the proposed JND CM processing. On this basis, a new blind image watermarking algorithm based on defocus JND estimation is proposed 11 . Zhang et al proposed a new block‐level perceptual image watermarking framework, including three‐directional correlation and block‐level JND models 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because a video can be regarded as a temporally continuous collection of still images, most image watermarking schemes [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] are also applicable for video watermarking. Existing image watermarking algorithms offer some ideas for resisting geometric attacks, and video watermarking can use these as references.…”
Section: Introductionmentioning
confidence: 99%